Polycomb repressive 2 complex—Molecular mechanisms of function. (10th June 2019) - Kouznetsova, Valentina L.; Tchekanov, Alex; Li, Xiaoming; Yan, Xiaowen; Tsigelny, Igor F.
Abstract: Numerous molecular processes conduct epigenetic regulation of protein transcription to maintain cell specification. In this review, we discuss molecular mechanisms of the Polycomb group of proteins and its enzymatic role in epigenetics. More specifically, we focus on the Polycomb repressive complex 2 (PRC2) and the effects of its repressive marker. We have compiled information regarding the biological structure and how that impacts the stability of the complex. In addition, we examined functions of the individual core proteins of PRC2 in relation to the accessory proteins that interact with the complex. Lastly, we discuss the implications of unregulated and downregulated PRC2 activity in Alzheimer's disease and cancer and possible methods of treatment related to PRC2 regulation.